2019
DOI: 10.1002/jor.24517
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Gender Have a Negative Impact on the Outcome of Hip Fracture Surgery—A Pilot Study

Abstract: Diabetes mellitus (DM) is associated with an elevated risk of post‐operative complications. The impact it has on patients living with DM following hip fracture surgery (HFS) is not completely understood and may represent a predictor of increased mortality. This study investigates the impact of DM, gender, American Society of Anaesthesiologists (ASA) grade, and fracture location, on the outcome of HFS in Ireland. The Hospital Inpatient Enquiry (HIPE) database records all fragility hip fractures within Galway Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In terms of the role of gender in diabetic osteopathy, the disorder follows an opposite pattern to that seen in CVD and DKD. Poor bone health experienced primarily by women in the non-DM population as they age is largely absent in men, but in the context of DM there is an increased relative risk for men to experience, for example, hip fracture [149,156]. Fractures such as these are associated with high morbidity, especially functional limitations that results in loss of independence -physically and economically [178].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of the role of gender in diabetic osteopathy, the disorder follows an opposite pattern to that seen in CVD and DKD. Poor bone health experienced primarily by women in the non-DM population as they age is largely absent in men, but in the context of DM there is an increased relative risk for men to experience, for example, hip fracture [149,156]. Fractures such as these are associated with high morbidity, especially functional limitations that results in loss of independence -physically and economically [178].…”
Section: Discussionmentioning
confidence: 99%
“…However, with an ageing population the absolute number of hip fractures is predicted to increase [139,140]. Compounding this challenge in managing orthopaedic health is the increased fracture risk in people living with T2DM [145][146][147][148][149]. Contrary to the osteoporotic context, this increase in fracture risk is despite generally increased BMD in the T2DM population [148,150,151].…”
Section: Diabetic Osteopathymentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, long-term exposure to the diabetic milieu elicits changes in bone metabolism and bone microarchitecture, which result in an increased risk of fracture and decreased healing rates [2,5,6]. Hip fractures are a significant basis of disability and mortality in middle-aged and older adults [7]. Previous studies have shown that both men and women with type 1 diabetes have low bone mineral density and an increased fracture risk [8][9][10].…”
Section: Introductionmentioning
confidence: 99%